PENGARUH EFIKASI DIRI, PERSEPSI KESEJAHTERAAN GURU, DAN PENGALAMAN PRAKTEK LAPANGAN KEPENDIDIKAN TERHADAP MINAT MENJADI GURU PADA MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS NEGERI PADANG - Fathia Muthmainah; Marwan Marwan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the extent to which self-efficacy, teachers’ perceptions of well-being, and educational fieldwork experiences influence the interest in becoming a teacher among Economics Education students at Padang State University. The underlying issue of this research stems from the disparity between the high number of education graduates and the low interest among some students in pursuing a career as a teacher, despite the high demand for educators in Indonesia. A quantitative approach using an associative method was employed. From a population of 141 students in the class of 2022, 105 respondents were selected using simple random sampling calculated with the Slovin formula. Data were collected using a questionnaire and analyzed using multiple linear regression in SPSS 21. The findings show that, collectively, the three variables have a positive and significant effect on the interest in becoming a teacher, accounting for 66.9% of the variance (R² = 0.669). Partially, all three variables were also significant and positive, with self-efficacy being the strongest factor (β = 0.595), followed by PLK experience (β = 0.190), and perceptions of teacher well-being (β = 0.139). These results indicate that fostering self-efficacy, improving the image of professional well-being, and providing high-quality teaching experiences are essential for encouraging students’ interest in pursuing a career as a teacher.